2015
DOI: 10.1136/sextrans-2015-052042
|View full text |Cite
|
Sign up to set email alerts
|

High HIV incidence among men who have sex with men attending a community-based voluntary counselling and testing service in Barcelona, Spain: results from the ITACA cohort

Abstract: The ITACA cohort revealed a high and increasing HIV incidence among MSM, especially important among foreign-born men. The findings underscore the need to implement multilevel interventions for MSM taking into account different types of partners, cultural origins and the exposure to other sexually transmitted infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…While these two studies employed a different methodology to estimate incidence, their results suggest that incidence has remained relatively stable and high over the past 10 years among men attending STI clinics [19]. Our estimates are also comparable with those for cohorts of MSM in Portugal (2.8 per 100 PY) [20], Spain (2.4 per 100 PY) [21], Germany (3.3%) [22] and the USA (2.4 per 100 PY) [23] but higher than that for clinic-attending MSM in Australia (1.3 per 100 PY) [24]. Different mathematical models have been developed to estimate HIV incidence among the general MSM population.…”
Section: Discussionsupporting
confidence: 69%
“…While these two studies employed a different methodology to estimate incidence, their results suggest that incidence has remained relatively stable and high over the past 10 years among men attending STI clinics [19]. Our estimates are also comparable with those for cohorts of MSM in Portugal (2.8 per 100 PY) [20], Spain (2.4 per 100 PY) [21], Germany (3.3%) [22] and the USA (2.4 per 100 PY) [23] but higher than that for clinic-attending MSM in Australia (1.3 per 100 PY) [24]. Different mathematical models have been developed to estimate HIV incidence among the general MSM population.…”
Section: Discussionsupporting
confidence: 69%
“…35 The ITACA cohort of 3544 MSM established in Barcelona, Spain, noted an overall HIV incidence of 2.4 per 100 person-years, with foreign born men being at increased risk for infection. 157 During the study period, HIV incidence increased from 1.2 to 3.1 person-years from 2009 to 2011.…”
Section: Current Hiv Incidence Data Among Men Who Have Sex With Men Imentioning
confidence: 94%
“…Studies have demonstrated MSM going to the sauna and seeking sexual partners through the internet were more likely to be younger and engage in high risk sexual behavior [20, 21]. Characteristics of sexual partnership have an impact upon risky behaviors and the majority of unprotected sex events occurring between steady/regular partners, this being associated with HIV seroincidence [2224]. Anal sex roles also contribute to high risk of HIV seroconversion especially among YMSM who adopt the receptive anal sex role without a condom [5, 25].…”
Section: Introductionmentioning
confidence: 99%